2019
DOI: 10.1088/1748-9326/aafa30
|View full text |Cite
|
Sign up to set email alerts
|

Just don’t call it climate change: climate-skeptic farmer adoption of climate-mitigative practices

Abstract: Despite low levels of agreement that climate change is caused primarily by humans, respondents to a survey of climate change beliefs and adoption of climate-mitigative practices among beef and grain producers in Alberta, Canada, indicate a high level of adoption of several agricultural practices with climate-mitigative benefits. Respondents' motivations for adoption of climate-mitigative practices rarely include the belief that climate change is caused by humans, but rather expectations for economic benefits, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 49 publications
0
26
0
1
Order By: Relevance
“…They affect production and management decisions both through a direct influence on productivity and through market prices. Understanding how such risks influence farmer decisions is increasingly important (Howden et al ; Ferraro, Messer, and Wu ; Davidson et al ).…”
Section: Emerging Focal Areas and Their Opportunitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…They affect production and management decisions both through a direct influence on productivity and through market prices. Understanding how such risks influence farmer decisions is increasingly important (Howden et al ; Ferraro, Messer, and Wu ; Davidson et al ).…”
Section: Emerging Focal Areas and Their Opportunitiesmentioning
confidence: 99%
“…This is a promising area for research at the intersection of agricultural adoption and behavioral risk modeling, that has potential to provide valuable insights about the policies that might encourage both individually and socially optimal farmer behavior. Moreover, some evidence from survey work suggests farmers perceive climate change risks differently to other sources of uncertainty (Davidson et al ). Research on agricultural adoption that embeds behavioral risk models may help identify opportunities for behavioral interventions, including nudges, that accelerate adoption of new technologies.…”
Section: Emerging Focal Areas and Their Opportunitiesmentioning
confidence: 99%
“…This study is in line with the findings from a study conducted in the Canadian oil and gas industry. The study reported that a firm and rule-oriented leadership, which is the main component for a good organizational climate, fostered strong compliance with rules and good safety behavior in the workers [64]. Furthermore, in another study, the researchers found that strong leaders will influence workers to cultivate positive communication, thus contributing to enhancing workers' commitment in regard to safety and disaster avoidance [18].…”
Section: Discussionmentioning
confidence: 96%
“…Arbuckle et al 2013; Chatrchyan et al 2017; Le Dang et al 2014), have focused on educating farmers about climate science, adhering to the (much-critiqued) "knowledge-de cit model" (Jasanoff 2003;McNeil 2013). This uni-directional knowledge transfer paradigm has not led to meaningful changes in land management practices, leaving scholars concerned about agriculture's ability to meet its mitigation and adaptation potential (Schewe and Stuart 2017;Inman et al 2018; Davidson et al 2019). To adapt to climate change effectively and equitably, researchers and policy makers must develop place-based strategies (Rojas-Downing et al 2017) and include farmers' experiences and beliefs in adaptation discourse (Soubry, Sherren, and Thornton 2020).…”
mentioning
confidence: 99%